Estudo das características funcionais de monócitos humanos infectados in vitro com diferentes cepas de Leishmania e análise da expressão dos transdutores de sinal e ativadores de transcrição (STATs) em linfócitos de indivíduos portadores de leishmaniose tegumentar americana - Agostinho Gonçalves Viana (2016)
Human infection with different Leishmania species leads to different clinical manifestations and clinical forms varying between the involvement of skin (L. braziliensis) and visceralization (L. infantum chagasi). These clinical manifestations have been related to different characteristics of the immune response of individuals who, while well studied, are not completely understood. Our work has hypothesized that infection of monocytes by different strains of Leishmania leads to differential expression of molecules associated with cellular activation and expression of cytokines, and that the presence of different cytokines in the microenvironment leads to changes in intracellular signaling cascades associated with clinical outcome. First, the expression of activation molecules and cytokine expression in infected peripheral blood mononuclear cells was evaluated in vitro with L. braziliensis (2904), a reference strain of L. chagasi (BH46) and a wild type strain of L. chagasi. These studies showed that the induction of TLR2, TLR9 and HLA-DR was lower in monocytes infected with L. chagasi compared with L. braziliensis. In addition, monocytes infected with the L. chagasi strains had a lower expression of TNF-, and a lower ratio TNF-/IL-10, resulting in a decrease in the inflammatory profile. Moreover, monocytes infected with L. chagasi were a 100 fold less effective at controlling Leishmania than cells infected with L. braziliensis. Evaluating the expression of activation molecules and cytokines by CD8+ T lymphocytes from the same cultures infected with the different Leishmania species, it was observed that infection with L. chagasi led to a decrease in the expression of IFN- and IL-17 comparing with L. braziliensis. Interestingly, the infection with strain L. chagasi BH46 led to an increase in the expression of the inhibitory molecule CTLA-4 on lymphocytes and infection by the same strain induced an increase of CD80 on monocytes. The L. braziliensis infection induced a more inflammatory profile in CD8+ T cells as seen by the increased expression of IFN- and IL-17, and also the cytotoxic molecule granzyme A, compared with infection by L. chagasi strains. Our results show that L. chagasi infection fails to induce a strong inflammatory response, as well as leads to less activation in monocytes and human lymphocytes, as compared to infection by L. braziliensis. This functional profile may help explain the different clinical outcome observed in patients infected with different species of Leishmania. Subsequently, we proposed to study the cellular response to cytokines through the analysis of the expression of phospho-STAT molecules in patients with cutaneous leishmaniasis. Our results showed an active role for STATs in an inflammatory environment with an increased expression of phospho-related inflammatory STATs (STAT-5), particularly in cells from patients with cutaneous leishmaniasis stimulated with Leishmania antigen. Furthermore, there was a decrease in the phospho-STAT related to an anti-inflammatory environment induced by IL-10 (STAT-3). These data are consistent with the observation that the environment seen in cutaneous leishmaniasis, indicates an active response by inflammatory cytokines, and that while IL-10 is present, its activity is decreased.